ANALISIS PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE PADA MATA PELAJARAN IPAS KELAS 4B SDN 6 MATARAM - Nurlaili, Nurlaili; Safitri, Riha; Latifa, Mutia; Dita, Ni Nyoman; Lustar Silia Nesa, Maria Oktaviani; Hidayat, Muhammad Hazrul; Istiningsih, Siti; Putri, Hikmah Ramdhani (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the application of the Learning Cycle learning model in the subject of Natural and Social Sciences (IPAS) in class IVB SDN 6 Mataram on the material of plant parts. The approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research subjects were all grade IVB students and grade IV teachers of SDN 6 Mataram. The results showed that the learning cycle model applied by the fourth grade teacher is the 5E leaning cycle model which consists of five stages namely engagement, exploration, explanation, elaboration, and evaluation. The application of this learning cycle model is able to increase students' involvement and motivation in the learning process. Students become more active, interested, and dare to try because they are directly involved in exploration and observation activities, so that understanding of the material becomes more meaningful and contextual. This model also encourages the development of critical thinking skills, scientific attitudes, and students' ability to build knowledge independently. However, the application of learning cycle faces several challenges, such as differences in students' learning styles, the ease of students' attention being distracted when learning outside the classroom, and environmental constraints such as unfavorable weather. Nonetheless, in general, the learning cycle model is effective in improving the quality of IPAS learning in class IVB SDN 6 Mataram, by providing an effective learning cycle for students.